Integrative analysis of immunogenic PANoptosis and experimental validation of cinobufagin-induced activation to enhance glioma immunotherapy - Yonghua Cai; Heng Xiao; Shuaishuai Xue; Peng Li; Zhengming Zhan; Jie Lin; Zibin Song; Jun Liu; Wei Xu; Qixiong Zhou; Songtao Qi; Xi’an Zhang; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Glioma, particularly glioblastoma (GBM), is a highly aggressive tumor with limited responsiveness to immunotherapy. PANoptosis, a form of programmed cell death merging pyroptosis, apoptosis, and necroptosis, plays an important role in reshaping the tumor microenvironment (TME) and enhancing immunotherapy effectiveness. This study investigates PANoptosis dynamics in glioma and explores the therapeutic potential of its activation, particularly through natural compounds such as cinobufagin. Methods We comprehensively analyzed PANoptosis-related genes (PANoRGs) in multiple glioma cohorts, identifying different PANoptosis patterns and constructing the PANoptosis enrichment score (PANoScore) to evaluate its relationship with patient prognosis and immune activity. Cinobufagin, identified as a PANoptosis activator, was evaluated for its ability to induce PANoptosis and enhance anti-tumor immune responses both in vitro and in vivo GBM models. Results Our findings indicate that high PANoScore gliomas showed increased immune cell infiltration, particularly effector T cells, and enhanced sensitivity to immunotherapies. Cinobufagin effectively induced PANoptosis, leading to increased immunogenic cell death, facilitated tumor-associated microglia/macrophages (TAMs) polarization towards an M1-like phenotype while augmenting CD4+/CD8 + T cell infiltration and activation. Importantly, cinobufagin combined with anti-PD-1 therapy exhibited significant synergistic effects and prolonged survival in GBM models. Conclusions These findings highlight the therapeutic potential of PANoptosis-targeting agents, such as cinobufagin, in combination with immunotherapy, offering a promising approach to convert “cold” tumors into “hot” ones and improving glioma treatment outcomes.